AB0675 RED CELL DISTRIBUTION WIDTH AND FATIGUE IN AXIAL SPONDYLOARTHRITIS: A SLEEPER SIGNAL. (2nd June 2020) - Chatterjee, S.; Wincup, C.; Rahman, A.; Sengupta, R.
Abstract : Background: Fatigue is a ubiquitous feature of autoimmune conditions, and axial Spondyloarthritis (axSpA) is no exception, with over 50% of patients reporting some degree of fatigue 1 . Erythrocyte size variability (as measured by red cell distribution width (RDW)) has been found to correlate with fatigue in a cohort of systemic lupus erythematous (SLE) patients and may reflect early iron deficiency 2 . We investigate whether this finding holds true in axSpA. Objectives: To investigate the relationships between fatigue, disease activity, and RDW (as a proxy for functional iron deficiency) in patients with axSpA. Methods: Cross-sectional analysis performed on patients with axSpA, as defined by the Assessment of SpondyloArthritis international Society (ASAS) criteria, enrolled in a longitudinal data collection study from October 2017 until January 2020 in a single outpatient setting. Patients required a minimum of 1 set of patient-reported outcome measures (PROMs), including the completion of a Functional Assessment of Chronic Fatigue Illness Therapy (FACIT) Fatigue Scale v4 (numerical score between 0–52 with a lower score indicating greater fatigue), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). C-reactive protein (CRP) as a biochemical marker of disease activity, as well as Haemoglobin (Hb) and RDW performed within 3 months either side of a PROMs set were extracted and matched. Only one pair of matched data was selected per patient according to the least timeframe between a set of PROMs and bloods of interest (if multiple were available). Anaemia was defined according to World Health Organisation criteria, i.e., Hb <120 g/L in females and Hb <130 g/L in males. Non-parametric analysis of variables was performed using Spearman's rank correlation with significance defined at a p-value <0.05. Results: 63 patients were included in the analysis (63.5% (40) male, mean time to diagnosis 11.46 (±9.04) years, 79.4% (50) HLA-B27 positive, 46% (29) current or ex-smokers). Blood parameters showed mean Hb of 139.6 (±16.03) g/L, mean RDW of 13.55 (±1.46) %, mean CRP of 5.23 (±10.82) mg/L. Mean BASDAI score of cohort was 3.69 (±2.02) and FACIT score 34.18 (±11.30). Mean absolute interval time difference between a PROMs set and bloods of interest was 16.14 (±41.11) days. Univariate analysis showed a statistically significant, negative correlation between fatigue (FACIT) and disease activity (BASDAI), (p<0.001; r= -0.63), but failed to demonstrate an association between fatigue and Hb, RDW, or CRP. Sub-group analysis of 51 patients, following exclusion of patients with anaemia (12), engendered a significant and moderately negative correlation between fatigue and RDW (p=0.02, r=-0.32) (Figure 1), maintained a significant correlation between fatigue and BASDAI (p<0.0001, r=-0.56) and showed a non-significant association between RDW and BASDAI (p=0.07, r=0.25). Conclusion: These findings suggest that RDW may potentially represent a surrogate marker of disease activity in patients with axSpA. RDW may also be implicated in the multi-faceted aetiology of fatigue in axSpA patients, and may reflect functional iron deficiency. A recent cohort study of axSpA patients found anti-TNF therapy ineffective at alleviating fatigue in nearly 80% of patients 1 . Management of potential functional iron deficiency as reflected by RDW may offer an alternative treatment target for fatigue in these patients. References: [1]Bedaiwi M, Sari I, Thavaneswaran A, et al. J Rheumatol. 2015;42(12):2354. [2]Wincup C, Parnell S, Cleanthous B, et al. Clin Exp Rheumatol. 2019 Sep-Oct;37(5):852-54. Disclosure of Interests: Saion Chatterjee: None declared, Chris Wincup: None declared, Anisur Rahman: None declared, Raj Sengupta Grant/research support from: Research grants from UCB, Pfizer, Abbvie and Novartis, Speakers bureau: Received honoraria for giving talks from Abbvie, Biogen, UCB, Novartis, Pfizer